The Implementation of Context Clues Strategy in Infering the Meaning of Unknown Vocabulary to Improve Reading Skill - Riska Mauliza; Iskandar Abdul Samad; Nira Erdiana (Universitas Syiah Kuala, 2020)
A key to reading comprehension is understanding the message conveyed and it depends heavily on the understanding of the meaning of words appeared in the text. For students, reading comprehension becomes one of the skills that they are more familiar with since they deal with reading texts every day even in examinations. This situation drives students to cope with many unfamiliar English words causing them stuck in comprehending the message conveyed. Therefore, assisting students to improve their comprehension by inferring word meaning from context is very important. Corresponding to the idea, the writer did an experimental study to implement context clues strategy which (is believed) can help students to infer words meaning in reading text. The study was implemented on 20 students of XII IPS3 of SMAN 12 Banda Aceh to figure out how the strategy assists the students in inferring the meaning of unknown words. The result shows that the students’ comprehension improves well reflected on the mean score got by students from pretest and posttest increasing from 54.5 to 80.25. The development can be achieved since the strategy trains and guides the students to find out the clues provided in the text in the form of definition, synonym, antonym, example, or inference, that help them to guess the meaning of the word. In conclusion, context clues strategy does assist the students in inferring words meaning from context. Hence, it is suggested for English teacher to apply it in classroom in order to facilitate students’ reading comprehension.